THE RELATIONSHIP OF HBA1C WITH VASCULAR FUNCTION USING FMD IN PATIENTS OF DIABETES MELITUS TYPE 2 IN RSLE PALEMBANG - Ahmad Khaeril Irfan; Erwin Sukandi; Dini Meta Rica (Majalah Kedokteran Sriwijaya, 2025)
In the pathophysiology of Diabetes Mellitus (DM) Type 2 there are glucotoxic and lipidotoxic conditions. This situation causes insulin resistance and pancreatic β cell damage that causes pancreatic β cell apoptosis. Then there will be an increase in free fatty acids (FFA), nitric oxide (NO) and blood sugar levels that cause endothelial dysfunction. High blood sugar levels will cause an increase in HbA1c levels, which will result in a decrease in FMD.Analyzing the relationship between HbA1c and vascular function using FMD in DM patients Type 2. The study used a correlative analytic design with a cross-sectional approach in the population of DM Type 2patients seeking treatment at Dr. Mohammad Hoesin Palembang from November 2019 to January 2020. The samples taken were patients who met the inclusion criteria and were willing to participate in the study by signing informed consent. All data were analyzed using the SPSS 22.0 for windows program. A total of 30 research subjects were obtained. There was a weak correlation between FMD and HbA1c (r = -0.365; p = 0.048). There is a significant correlation with weak strength between FMD values ​​and HbA1c levels in DM patients Type 2